Freestanding Thin‐Films: Water‐Assisted Liftoff of Polycrystalline CdS/CdTe Thin Films Using Heterogeneous Interfacial Engineering (Adv. Mater. Interfaces 14/2019). Issue 14 (23rd July 2019) - Magginetti, David J.; Aguiar, Jeffery A.; Winger, Joshua R.; Scarpulla, Michael A.; Pourshaban, Erfan; Yoon, Heayoung P.
Abstract : In article number1900300, David J. Magginetti, Jeffery Aguiar, Heayoung P. Yoon, and co‐workers show a new synthesis method that allows the high‐temperature processing for grain growth of CdS/CdTe, while enabling simple liftoff in water at room temperature. Such freestanding CdS/CdTe thin films can be integrated onto low‐cost flexible substrates that have a limited temperature tolerance.